1992
DOI: 10.1021/j100191a075
|View full text |Cite
|
Sign up to set email alerts
|

Studies on sodium ricinoleate. 1. Adsorption and aggregation behavior

Abstract: Adsorption at the air-water interface and aggregation in dilute solutions of sodium ricinoleate (sodium 12-hydroxy-cis-9-octadecenoate) (NaR) have been investigated. The mid-chain polarity due to the presence of a double bond and hydroxy group have a profound influence on the dilute solution properties of NaR. The area per molecule obtained at the air-water interface (1.06 nm2) suggests that the molecule takes up a wicket shape with both carboxyl and hydroxyl groups residing at the interface. Studies on the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 4 publications
5
15
0
Order By: Relevance
“…[60] If such ah ypothesis does not seem, to the best of our knowledge,t oh ave been proposed before, older studies aiminga te lucidating the structure of micelles composed of bolaform surfactants do not always agree on the intramicelle molecular conformation. Although recent works by Davey et al [56] and Shinde and Narayan [57] propose, for alcohol derivatives of alkylammonium bromides and sodium oleate, respectively,ahomogeneous micellar structure in which the alcohol groups are in contact with the solvent, by either molecular folding or micellar crossing, older studies seem to state that alcohol and ketonef unctions in alkylammonium boaamphiphile derivatives reside in the aliphatic core of the micelle instead. [63,64] We then believe that, at the actual state of the art, there is great room for improvementi nt he precise descriptiono fb olaamphiphile micelles, but this is not the goal of this work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[60] If such ah ypothesis does not seem, to the best of our knowledge,t oh ave been proposed before, older studies aiminga te lucidating the structure of micelles composed of bolaform surfactants do not always agree on the intramicelle molecular conformation. Although recent works by Davey et al [56] and Shinde and Narayan [57] propose, for alcohol derivatives of alkylammonium bromides and sodium oleate, respectively,ahomogeneous micellar structure in which the alcohol groups are in contact with the solvent, by either molecular folding or micellar crossing, older studies seem to state that alcohol and ketonef unctions in alkylammonium boaamphiphile derivatives reside in the aliphatic core of the micelle instead. [63,64] We then believe that, at the actual state of the art, there is great room for improvementi nt he precise descriptiono fb olaamphiphile micelles, but this is not the goal of this work.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Accordingly,e ven if currently we cannot provide anyd irect spectroscopicp roof, we propose the hypothesis that the platelets are composed of at least amonolayer of SL molecules in ah ead-to-tail conformation to minimize repulsion between adjacent negative charges through the intercalation of as ophorose moiety.T he same head-to-tail conformation is believed to be part of the twisted ribbons tructure composed of SL C18:0 under neutrala nd acidic pH conditions. [38] Other reports on alcohol derivatives of alkylammonium [56] and oleate [57] salt bolaamphiphiles, which are interesting compounds to cite because they have as imilar neutral-ionic bolaform structure to that of SLs under basic pH conditions,h ave shownt he formation of micelles,e ven if one would have expectedf lat structures from simple geometric considerations: the OH group, which is less bulky than sophorose, would be responsible for al arger packing parametert hat is typical of less curbed morphologies. However,t he interesting common point between our study and theirsist he fact that micelles are found to coexistw ith platelets, as discussed in the following paragraphs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large amount of work has been dedicated to the synthesis and characterization of bola systems; however, much less work has been devoted to a thorough structural study. In the context of micellar objects composed of bolaamphiphiles, ,, advanced structural considerations of the micellar packing and bola distribution are rare. , Indeed, Nagarajan predicted the formation and structure of micelles composed of bolaamphiphiles, basing his hypotheses on the analysis of the packing parameter. Interestingly, he predicted the formation of spherical, cylindrical, and discoidal micelles, in which he imagined that the bolaform compound has two configurations: elongated, which induces transradial crossing of the end-groups; folded, under which the end-groups lie both on the same side.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al have made progress with macroscopical verification of Nagarajan’s assumptions by observing a pH/cosolvent-driven tube-to-vesicle-to-micelle transition in disodium phenyl-1,4-bis­(oxyhexanoate) solutions, although the actual bola distribution within the micelle was never elucidated. Additional insights in the structural composition of bola-composed micelles have been discussed in refs , , mainly using small-angle neutron scattering (SANS) and/or self-diffusion nuclear magnetic resonance (NMR) experiments. However, in practically all cases, these experiments have been used to describe the micellar shape and size.…”
Section: Introductionmentioning
confidence: 99%